Non-canonical Wnt/Ca2+ signaling is essential to promote self-renewal and proliferation in colon cancer stem cells - Sarabia-Sánchez, Miguel Angel; Moreno-Londoño, Angela Patricia; Castañeda-Patlán, María Cristina; Alvarado-Ortiz, Eduardo; Martínez-Morales, Juan Carlos; Robles-Flores, Martha (Frontiers in Oncology, 2023)
Cancer Stem Cells (CSC) are responsible for maintaining tumor growth, chemoresistance, and metastasis. Therefore, understanding their characteristics is critical to progress in cancer therapy. While the contribution of the canonical Wnt/-catenin signaling in both normal and CSCs had been well established, the function of non-canonical Wnt signaling cascades in stem cells is unclear. Recently, we reported that Wnt ligands trigger complex signaling in which the canonical and non-canonical responses can be simultaneously activated by one ligand in colon cancer cells, suggesting, therefore, that non-canonical Wnt pathways may also be important in CSCs. The present work aimed to know the role of the Wnt/Ca2+ pathway in colon CSCs. We used tumorspheres as a model of CSCs enrichment of CRC cell lines with different Wnt/β-catenin contexts. Using Wnt3a and Wnt5a as prototype ligands to activate the canonical or the non-canonical pathways, respectively, we found that both Wnt3a and Wnt5a promote sphere-formation capacity and proliferation without stimulating β-catenin-dependent transcription. Upregulation of sphere formation by Wnt5a or Wnt3a requires the downstream activation of Phospholipase C and transcriptional factor NFAT. Moreover, the single specific inhibition of PLC or NFAT, using U73122 and 11R-VIVIT, respectively, leads to impaired sphere formation. Our results indicate that both types of ligands activate the Wnt/Ca2+ signaling axis to induce/maintain the self-renewal efficiency of CSCs, demonstrating to be essential for the functions of CSC in colon cancer.